OPTIMALISASI POTENSI PARIWISATA TAMAN KELINCI DESA DAWUHANSENGON KABUPATEN PASURUAN - Fikri, M. Andi; Teaningrum , Ratna Yulis (Journal of Social Comunity Services, 2024)
One of the activities that is a superior program in the Enlightenment Real Work Lecture (KKN-P) is optimizing the tourism potential of Rabbit Park in Dawuhansengon Village, Pasuruan Regency. The main problems faced are the lack of care for rabbit parks and lack of accessibility, so many people do not know about their existence. This research was conducted using the community service method through the Enlightenment Real Work Lecture (KKN-P) program conducted by students at Muhammadiyah University of Sidoarjo. The methods used include group debriefing, field surveys, preparation of work programs, and implementation of work programs. Actions taken include cleaning the park, making fences, signposts, road signs and repainting. The results of this program show that the improvements made by KKN-P students have had a positive impact on the condition of Rabbit Park and increased public interest in visiting the place. The village and local government need to provide support in optimizing the tourism sector in Dawuhansengon Village by improving access and marketing of Rabbit Park as well as organizing various tourism events that can attract tourist interest. Keywords: optimizing, potential, tourism